Interactive Geography Learning Integrated with Game-Based Learning using Augmented Reality for Generation Zilenial at Tourist Destinations in the City of Makassar - Muhammad Fauzi; Dean Gery Pasamba; Nabil Habib Makalalag (Journal of Geosciences and Environmental Studies, 2026)
A significant challenge in contemporary education is the low level of geographical literacy among Generation Z, which is often exacerbated by conventional teaching methods. This study aims to develop and evaluate a digital geography learning framework that integrates Augmented Reality (AR) with Game-Based Learning, specifically tailored for Generation Z in tourist destinations in Makassar City. The primary objective is to assess the viability of this approach for enhancing engagement in learning. A mixed-methods approach was employed, incorporating quantitative data from a questionnaire survey of 46 respondents and qualitative data from a literature review. The findings reveal that 93.6% of participants expressed a strong interest in implementing AR-based Game-Based Learning at local attractions such as Losari Beach. In conclusion, the integration of AR with Game-Based Learning significantly enhances the interactivity and appeal of geography education for the Generation Zilenial demographic.